2009
DOI: 10.1002/hon.922
|View full text |Cite
|
Sign up to set email alerts
|

Clofarabine in the treatment of poor risk acute myeloid leukaemia

Abstract: Clofarabine is a second generation nucleoside analogue. It inhibits DNA repair and activates the mitochondrial apoptotic pathway leading to cell death. In vitro clofarabine has demonstrated synergy with daunorubicin and Ara-C and in phase II clinical trials has shown promising activity in poor risk Acute myeloid leukaemia (AML) patients. In our institution over a 24 month period 22 AML patients (11 M, 11 F) with poor risk features, deemed unsuitable for standard therapy, were treated with clofarabine, alone (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The role of IV single-agent clofarabine was also studied in a smaller cohort of patients with AML with poor risk features, deemed unsuitable for standard therapy [26]. Twenty-two patients were treated with clofarabine, alone (eight patients) or in combination (14 patients) for up to three cycles of treatment.…”
Section: Clofarabine Experience In Adultsmentioning
confidence: 99%
“…The role of IV single-agent clofarabine was also studied in a smaller cohort of patients with AML with poor risk features, deemed unsuitable for standard therapy [26]. Twenty-two patients were treated with clofarabine, alone (eight patients) or in combination (14 patients) for up to three cycles of treatment.…”
Section: Clofarabine Experience In Adultsmentioning
confidence: 99%
“…Clofarabine, a second generation nucleoside analog, has shown activity in patients with relapsed or refractory acute myeloid leukemia in younger and older patients as a single agent and in combination with high dose ARA-C. Krawczyk et al, 2010;Tse et al, 2011). A recent review of clofarabine in the elderly patients with AML revealed that clofarabine may be appropriate in a subset of patients with poor performance status and cardiovascular disease, not fit for intensive chemotherapy (Tran and Yang, 2012).…”
Section: 1089 Clofarabine Suitability For Elderly Patients With Acutmentioning
confidence: 99%
“…Clofarabine has also shown activity in combination with high dose ARA-C in relapsed or refractory younger and older patients with AML (Tse et al, 2011). Most of the studies published previously come from limited centers from the US or Europe and there is a lack of experience with this drug in the community setting (Krawczyk et al, 2010). Here we describe our experience in the elderly AML patients treated with clofarabine.…”
Section: Introductionmentioning
confidence: 97%
“…Kassim et al (2005). Additionally, Clofarabine should be considered for elderly patients as they are often not considered suitable transplant candidates and they often present with unfavorable risk disease (Krawczyk et al, 2010).…”
Section: Treatment Of Amlmentioning
confidence: 99%